2018
DOI: 10.21470/1678-9741-2017-0224
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple Valve Replacement for Carcinoid Heart Disease

Abstract: IntroductionCarcinoid heart disease most frequently involves the tricuspid or, more rarely, the pulmonary valve and presents with right heart failure as 5-HT is metabolized by the lung. Left-sided valve involvement is quite rare. We describe our experience of 3 patients presenting with heart failure secondary to carcinoid heart disease affecting all four cardiac valves. There are only four previous isolated case reports in the literature.MethodsAll three patients underwent quadruple valve replacement during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Seven patients were reported from the Mayo Clinic ( 6 ), almost all of whom had mechanical valves implanted. To the best of the present authors’ knowledge, quadruple valve replacement with all bioprosthetic valves has been reported in only 1 previous patient ( 7 ). Conventionally, the present authors use bioprosthetic valves in CaHD patients who have limited life expectancy and may not manage warfarin therapy well due to hepatic tumor burden.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Seven patients were reported from the Mayo Clinic ( 6 ), almost all of whom had mechanical valves implanted. To the best of the present authors’ knowledge, quadruple valve replacement with all bioprosthetic valves has been reported in only 1 previous patient ( 7 ). Conventionally, the present authors use bioprosthetic valves in CaHD patients who have limited life expectancy and may not manage warfarin therapy well due to hepatic tumor burden.…”
Section: Discussionmentioning
confidence: 87%
“…Quadruple valve surgery in CaHD has previously been described in only a few case series ( 5 , 6 , 7 ). Castillo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac involvement in carcinoid syndrome portends a worse prognosis and overall mortality with an estimated three-year survival is 31% with cardiac involvement compared to 68% [2]. When identified, surgery has shown to improve morbidity with post-operative reductions in NYHA heart failure class [6]. The second unique feature of this case was early imaging findings that confounded the final diagnosis of intrapulmonary shunt.…”
Section: Discussionmentioning
confidence: 87%
“…En casos avanzados, refractarios a la terapia médica y en quienes el compromiso valvular severo contraindique procedimientos quirúrgicos (cirugías hepáticas), la cirugía cardiovascular es una opción (22)(23)(24)(25). La decisión entre bioprótesis o prótesis mecánica debe ser individualizada; sin embargo, debido al alto riesgo de sangrado (aún más ante la presencia de metástasis hepáticas), las bioprótesis son más usadas y recientemente, el reemplazo valvular percutáneo comienza a mostrarse como una opción adicional (4,26).…”
Section: Discussionunclassified